Glocalisation of personal ads - gender identity construction of Malaysia adolescents - Bahiyah Dato‟ Hj. Abdul Hamid,; Kesumawati A. Bakar, (2007)
Globalisation and glocalisation of ads are observed to operate at two textual levels. The first level concerns the schematic genre while the second concerns the syntactic structure of personal ads. This article examines the process of homogenisation via conformity to the schematic structure of personal ads. Through a quantitative and qualitative analyses of adolescents‟ ads, findings demonstrate how adolescent advertisers stretch the boundaries of the personal ad genre, negotiate normative constraints on their communicative task. The findings of this study showed that Malaysian adolescents are not constantly confused and ambivalent of their personal identity.